A case report on limitation of mouth opening as somatization of major depressive disorder - Hasegawa, Isao; Ishii, Takashi; Suzuki, Akira; Miyauchi, Midori; Yoshida, Kazumasa; Karibe, Hiroyuki; Satoh, Tazuko; Ogawa, Tomohisa; Oshima, Katsuro; Ohtsu, Mitsuhiro; Okada, Tomoo; Ide, Masatoshi; et al. (Japanese Journal of Psychosomatic Dentistry, 2006)
We report a case of restricted mouth opening as somatization of a major depressive disorder. The patient was a 59 year old female who had her lower right third molar extracted at a dental clinic in March of the year in question and began to experience restricted mouth opening one month later. The clinic introduced her to the oral surgery department of a hospital but, despite many tests there, no physical disease was found. Her symptoms became worse in the October but a second dental clinic also found no abnormality in her mouth. She then visited the Nippon Dental University Hospital in December of the same year. Rather than performing X-rays and other physical examinations, we commenced with a medical interview. Her complaint was that she could no longer open her mouth properly since her dental treatment. She had, however, also been experiencing domestic problems that corresponded chronologically to the onset of her mouth opening problem and a number of factors satisfied the diagnostic criteria of a major depressive episode (DSM-IV-TR). Suspecting the somatization of a major depressive disorder, we introduced her to a psychiatrist who confirmed that diagnosis and undertook psychotherapy. Her mouth opening performance has improved as a result. We suggest that it is important to bear in mind that dental symptoms may be due to a mental disease and arrange for early referral to a psychiatrist when this is suspected.